(3GdeYde Ydi MQha GdeYLes - (3GHf ZfGe , EHQGgje Hf jMji Hf ZfGe GdMQGfj GdebOSj GdfejQj, CHh WGgQ,J (B779 (3g` s ((3eMeO Hf Ydi Hf SdGe s)
(3ChdgG (B:s
(3hHYO deG QCjJ cKjQG ef GdeYHQjf GdeDdajf GdcJH ddSGFdjf ef GdeNJUQGJ hGdeWhdGJ s
(3BNQgG (B:s
(3dGf GdcJGHI MjdI hde CLO ai MQa GdCda hGddGe GdeQcH hdG ai GdjGA TjFkG s
(3GfXQ GjVG ai GNJUGQ GdeYde HQbe (B13s
(3ai JYHjQ GdQDjGs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B80 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B126s
Keywords: (3JYHjQ GdQDjGs